2020
DOI: 10.1021/acschembio.0c00900
|View full text |Cite
|
Sign up to set email alerts
|

Protein Folding Stability Changes Across the Proteome Reveal Targets of Cu Toxicity in E. coli

Abstract: The ability of metal ionophores to induce cellular metal hyperaccumulation endows them with potent antimicrobial activity; however, the targets and mechanisms behind these outcomes are not well understood. This work describes the first utilization of proteome-wide measurements of protein folding stability in combination with protein expression level analysis to identify protein targets of copper, thereby providing new insight into ionophore-induced copper toxicity in E. coli. The protein folding stability anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 54 publications
3
37
0
Order By: Relevance
“…Evidence for Cu’s toxic effects is abundant, and its direct impact on the proteins required for metabolism, respiration, and protein synthesis is steadily emerging, as revealed, for example, by a study in Staphylococcus aureus that found that Cu stress targets proteins involved in central carbon metabolism [ 61 ]. Additionally, a recent proteomics study from one of us used protein folding stability measurements to identify protein hits of pyrithione in combination with Cu [ 33 ]. In that study, we found a number of protein hits involved in glycolysis, the citric acid cycle, and protein biosynthesis that were distinctly driven by the Cu delivered to the cell by pyrithione [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Evidence for Cu’s toxic effects is abundant, and its direct impact on the proteins required for metabolism, respiration, and protein synthesis is steadily emerging, as revealed, for example, by a study in Staphylococcus aureus that found that Cu stress targets proteins involved in central carbon metabolism [ 61 ]. Additionally, a recent proteomics study from one of us used protein folding stability measurements to identify protein hits of pyrithione in combination with Cu [ 33 ]. In that study, we found a number of protein hits involved in glycolysis, the citric acid cycle, and protein biosynthesis that were distinctly driven by the Cu delivered to the cell by pyrithione [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent proteomics study from one of us used protein folding stability measurements to identify protein hits of pyrithione in combination with Cu [ 33 ]. In that study, we found a number of protein hits involved in glycolysis, the citric acid cycle, and protein biosynthesis that were distinctly driven by the Cu delivered to the cell by pyrithione [ 33 ]. In the context of the current results identifying the ΔcopA knockout strain as highly sensitive to pyrithione, a picture emerges that pyrithione’s mechanism of action is directly linked to its facilitation of Cu gaining unregulated access to the cytoplasm of E. coli , consistent with its activity in yeast [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations